2020
DOI: 10.3332/ecancer.2020.1045
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-infiltrating Langerhans cells in non-melanoma skin cancer, a clinical and immunohistochemical study

Abstract: Non-melanoma skin cancer, including basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) represents 78.5% of all skin malignant tumours in Egypt. Dendritic cells can be found in almost all human tumours, they play an important role in antitumour immunity. The aim of the present study was to evaluate the percentage of Langerhans cells using CD1a in non-melanoma skin cancer, including BCC and SCC and to correlate this percentage with their clinicopathological features. The current study was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Moreover, the percentages of LCs are higher in healthy epidermis when compared to the adjacent epidermis, flanking the tumoral tissue, and to the intratumoral tissue. Furthermore, the percentages of LCs are higher in BCC than in SCC [56]. In contrast, our data show very few LCs within the tumoral mass of BCC (Figure 3), as opposed to SCC, where LCs are relatively abundant (Figure 4).…”
Section: Skin Cancerscontrasting
confidence: 68%
“…Moreover, the percentages of LCs are higher in healthy epidermis when compared to the adjacent epidermis, flanking the tumoral tissue, and to the intratumoral tissue. Furthermore, the percentages of LCs are higher in BCC than in SCC [56]. In contrast, our data show very few LCs within the tumoral mass of BCC (Figure 3), as opposed to SCC, where LCs are relatively abundant (Figure 4).…”
Section: Skin Cancerscontrasting
confidence: 68%
“…To our knowledge, LC count was not investigated before in BCC of XP patients; however, it was reported to be of lower density with morphologic changes in the BCC lesions of normal individuals compared with normal skin. 9,11,[22][23][24][25] Furthermore, UV exposure not only affects the LCs numbers but also affects their antigen-presenting capacity. UV-irradiated LCs present antigens to Th2 cells, but fail to activate Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These data explain the results proven in the present study in which the LCs count at the 3 different areas (intratumoral, peritumoral, and perilesional epidermis) were of significantly lower mean values in XP patients compared with non-XP controls. To our knowledge, LC count was not investigated before in BCC of XP patients; however, it was reported to be of lower density with morphologic changes in the BCC lesions of normal individuals compared with normal skin 9,11,22–25…”
Section: Discussionmentioning
confidence: 99%
“…Similar to LC in mice, human LC reside in the basal and supra-basal layers of the epidermis, where they form a dense network of first-line defense against invading pathogens. A recent study compared LC frequencies in 41 human non-melanoma tumor lesions and 16 healthy control tissues, revealing significantly decreased LC frequencies in tumor tissue and adjacent epidermis overlying malignant tissue compared to healthy skin; additionally, squamous cell carcinoma (SCC) lesions showed a more dramatic decrease of LC than that of basal cell carcinoma (BCC) lesions [95]. Consistent with this report, a systematic review of available nonmelanoma skin cancer-related studies was performed and quantitatively assessed LC in nonmelanoma skin cancers and identified an overall trend towards slightly higher numbers of LC in BCC than in SCC lesions, although there were discrepancies between individual studies [96].…”
Section: Langerhans Cells In Skin Cancer Development and Progressionmentioning
confidence: 99%